2010
DOI: 10.1111/j.1365-2788.2009.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intellectual disabilities in Norway: Domestic variance

Abstract: Based on national registers, the prevalence of intellectual disability (ID) in Norway is estimated to be 0.44 per 100 inhabitants. This study aimed to examine geographic and urban-rural differences in the prevalence of ID in Norway. Methods A survey based on the national register. Financial transfers intended to provide equal services to people with ID are based on these reports. Results A higher prevalence was found in the North region of Norway. A negative correlation between the population density and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
0
30
0
2
Order By: Relevance
“…Variations in prevalence across countries are linked to different methods of case ascertainment, inclusion/exclusion criteria and classification (Fujiura & Taylor 2003; Leonard et al . 2003; NHS Health Scotland 2004; Emerson & Hatton 2008; Søndenaa et al . 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in prevalence across countries are linked to different methods of case ascertainment, inclusion/exclusion criteria and classification (Fujiura & Taylor 2003; Leonard et al . 2003; NHS Health Scotland 2004; Emerson & Hatton 2008; Søndenaa et al . 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Norway, only 0.4% of the population is registered with an ID (Søndenaa et al 2010), and as in the world in general, the exact number of people with mild IDs in Norway is unknown. However, in Norway, only 0.4% of the population is registered with an ID (Søndenaa et al 2010), and as in the world in general, the exact number of people with mild IDs in Norway is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In most countries, it is difficult to identify people with an intelligence quotient at the border for diagnosis of mild ID (Søndenaa et al 2010;Maulik et al 2011). In most countries, it is difficult to identify people with an intelligence quotient at the border for diagnosis of mild ID (Søndenaa et al 2010;Maulik et al 2011).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The geographical distribution of individuals with ID in our study, which indicated a higher prevalence in northern Sweden, is quite similar to patterns observed in Norway, where a higher prevalence was also observed in the northern Norwegian region which has less population density (Sondenaa et al . ). In addition to the geographical discrepancies observed in the prevalence of older individuals with ID who accessed the LSS service, there were also geographical differences in the incidence of inpatient diagnoses related to ID.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study based on the national registers in Norway showed that the prevalence of ID was as high as 440 per 100 000 population (Sondenaa et al . ). Comparable estimates across studies and countries are difficult to obtain because of different study designs, sampling processes and study populations employed in the studies.…”
Section: Introductionmentioning
confidence: 97%